(3GdEbfGY aj GdbQAGJ GdSHYs - (3GHf GdHGPT , CMeO Hf Ydj Hf CMeO Hf Nda GdCfUGQj GdZQfGWj, CHh LYaQ,J (B540 (3g` s
(3ChdgG (B:s
(3bGd GdCSJGP GdGLd CHh LYaQ CMeO Hf Ydi GdebQi (B: (3GdMeO ddg GdPi Yde jLeY GdYde dEfSGf hdG bUOg Ydi ecGf s
(3BNQgG (B:s
(3Yf bJGOI Yf CfS Hf eGdc Yf GdfHi Udi Gddg Ydjg hSde bGd (B: (3eY cd NJeI OYhI eSJLGHI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B316s
Keywords: (3GdbQGAGJ hGdJLhjOs